Pengaruh Usefulness Dan Ease of Use Terhadap Online Booking Hotel Intention di Platform Agoda - Anisa, Armi; Wulansari, Nidia; Saladin, khairani (Departemen Pariwisata Universitas Negeri Padang, 2023)
This research is driven by the researcher's observations concerning online hotel booking intention on the Agoda platform. The development of guest visit rates has experienced a significant decline, with fewer guests opting to check in using the Agoda platform compared to other online travel agents. This is influenced by the perceived lack of usefulness and ease of use on the Agoda website. The objective of this study is to describe and analyze the impact of usefulness and ease of use on online hotel booking intention on the Agoda platform. The research methodology employed is quantitative research using purposive sampling, with a sample size of 130 respondents determined using the Hair formula. Data collection in this study utilized a questionnaire with a Likert scale that had been tested for validity and reliability. The collected data was analyzed using multiple linear regression analysis with the assistance of SPSS (Statistical Product and Service Solution) version 27.00. Based on the research analysis, it can be concluded that the independent variables, usefulness (X1) and ease of use (X2), have a positive and significant influence on the dependent variable, which is online hotel booking intention. Usefulness (X1) and ease of use (X2) collectively account for 24.7% of the variance in online hotel booking intention (Y), while the remaining 75.3% is influenced by other variables.